Agrobacterium mediated transformation of two peanut (Arachis hypogaea L.) explants using Na⁺/H⁺ antiporter gene to generate transgenies to resist salinity stress - Jahan, Noor (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.